Socially Necessary Green Development in India - Azad, Rohit; Chakraborty, Shouvik (Development and change, 2025)
Inequality and climate change are intricately linked, both in terms of the cause and the effect of climate change. The insight that inequality in emissions goes hand in hand with rising socio‐economic inequality gives the impression that this is a straightforward, positive relationship, giving rise to the assumption that a mere redistribution of income in favour of the poor and disadvantaged will reverse the climate crisis. Focusing on the Indian context, this article shows that this may be an erroneous assumption. A redistribution of income in favour of those at the lower end of the population may actually lead to higher emissions per capita — the carbon inequality paradox. However, this does not mean that a choice has to be made between emissions and equality. While energy may be required for an egalitarian development, the source of that energy need not be dirty. The authors argue that a green energy transition is vital for any progressive fight against the twin problems of rising emissions and inequality. They propose a green development programme which, as well as promoting this energy transition, encourages socially necessary consumption through state‐led expenditure programmes while socially unnecessary expenses of the elite are reined in through aggressive direct and indirect taxes.